Technical Note: Effect of transducer position and ground plane configuration on image quality in MR‐guided focused ultrasound therapies. Issue 6 (6th April 2020) - Payne, Allison; Minalga, Emilee; Merrill, Robb; Parker, Dennis L.; Hadley, J. Rock
Abstract : Purpose: To evaluate the effect of a focused ultrasound transducer position and ground plane configuration on magnetic resonance image quality. Methods: The effect of transducer position with respect to the MRI B0 field and the radiofrequency receive coils was evaluated in a breast‐specific MRgFUS system with an integrated RF phased‐array coil. Image signal‐to‐noise ratio was evaluated at different transducer locations. The effect of ultrasound transducer ground plane configuration was evaluated using a replica transducer with 12 ground plane configurations. All evaluations were performed at 3 Tesla. Results: Both transducer position and ground plane configuration were found to have a considerable effect on overall image SNR. A 67% increase in SNR was achieved by positioning the transducer face perpendicular to the B0 field. A 25% increase in SNR was achieved by segmenting the replica transducer ground plane from one continuous plane to nine individual segments. Conclusions: Advances in focused ultrasound hardware allow for integrated radiofrequency MRI coils as well as adjustable transducer positioning. The placement of the ultrasound transducer with respect to both the magnetic field and RF coils can have a considerable effect on image SNR and the resulting MR images that are used for MR‐guided focused ultrasound treatment planning, monitoring and assessment. Abstract :